PTH-040 Laparoscopic-assisted colonoscopic polypectomy is a safe and effective option for difficult polyps: a single tertiary referral centre experience. (22nd June 2015) - Garg, M; Tsiamoulos, Z; Rameshshanker, R; Beintaris, I; Spranger, H; Rajendran, A; Faiz, O; Antoniou, A; Warusavitarne, J; Saunders, BP
Abstract : Introduction: Colonic polyps deemed difficult to access or resect at endoscopy are often referred for surgical resection. We report our experience using laparoscopic assisted colonoscopic polyp resection at a single tertiary referral centre. Method: Combined procedures from 2012 to 2014 for patients referred for resection of colonic polypsons deemed not amenable for safe endoscopic resection or where access was difficult, and therefore planned for laparoscopic assistance, were analysed. Clinical data regarding primary lesion, reason for referral for laparoscopic assistance, and outcomes were recorded. Results: 15 patients have so far been planned for laparo-endoscopic procedures following multidisciplinary meetings, of whom 1 patient proceeded with surgery alone. 14 patients, with median age 73.0 years (range 35.7–85.1 years) were studied. The main reasons for laparoscopic assistance were: large high risk polyps, unfavourable location and the presence of diverticular disease. The median size of the polyps was 5 cm (range 2.3–15 cm). All procedures were performed under general anaesthetic. Completion of colonoscopic resection was performed with surgical presence without laparoscopic assistance in one. Laparoscopic adhesiolysis was performed in 5 patients to facilitate access. Seven patients required surgical resection (laparoscopic right hemicolectomy in 6 and sigmoid resection in 1). A cancer was confirmed histologically in 3 of these patients, with the other four being adenomas with high-grade dysplasia (HGD, 1) or low grade dysplasia (LGD, 3). In the remaining 7 patients, complete polypectomy was achieved, with histopathology showing adenomas with HGD (2), LGD (1), and lipomas in 3 patients with submucosal lesions, and non-diagnostic material in one patient. Median post-operative length of stay was 2 days (range 1 to 5 days) following colonoscopic resection, and uncomplicated except for post-polypectomy syndrome in one patient. Three of these patients have been followed-up to 6 months, with no recurrence of the lesion seen. Amongst patients requiring surgical resection, length of stay was longer (median 6 days [range 3–21 days], p = 0.002, Mann Whitney), with one patient suffering from anastomotic leak and another from an intra-abdominal fluid collection managed conservatively. Conclusion: Attempted laparoscopic-assisted colonoscopic polypectomy is an effective strategy in a selected patients, enabling safe and complete polypectomy for lesions that are difficult to resect at primary colonoscopy. This approach may help to reduce surgical morbidity and reduce length of hospital stay. Disclosure of interest: None Declared.